2014
DOI: 10.4314/star.v3i2.22
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Mycobacterium Tuberculosis Complex at Nekemte Municipality Abattoir, Western Ethiopia

Abstract: Article Information A cross-sectional study was conducted at Nekemte Manicipality Abattoir from September 2009 to May 2010 to estimate the prevalence of bovine tuberculosis (BTB), and characterize its causative agents. Post mortem examination, bacteriological culturing, Zeihl Neelsen staining, multiplex polymerase chain reaction (PCR), and region of difference-4 (RD4) deletion typing were used for investigation. Cattles (1168) were recruited for the study and the prevalence was found to be 5.9% (70/1186) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
4
5
1
Order By: Relevance
“…The present study showed that crossbred cattle were found to be more susceptible to bovine tuberculosis (BTB) than local zebu breeds. This finding was consistent with results from previous studies, such as [ 13 ], which reported a 17.9% prevalence of BTB in crossbreeds and 4.4% in the local breeds, and similar findings were also reported by [ 18 , 23 , 47 49 ] across different Ethiopian abattoirs, which indicated that crossbreeds are more at risk for BTB clinical disease than Zebus.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study showed that crossbred cattle were found to be more susceptible to bovine tuberculosis (BTB) than local zebu breeds. This finding was consistent with results from previous studies, such as [ 13 ], which reported a 17.9% prevalence of BTB in crossbreeds and 4.4% in the local breeds, and similar findings were also reported by [ 18 , 23 , 47 49 ] across different Ethiopian abattoirs, which indicated that crossbreeds are more at risk for BTB clinical disease than Zebus.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, sex was not a risk factor for tuberculosis lesions, consistent with studies by [ 11 , 23 , 49 ] from Ethiopian abattoirs. However, Shewatatek [ 48 ] found that sex was a risk factor for bovine tuberculosis in North Gondar.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Teklu et al, 33 indicated the presence of caseous and/or calcified lesions may not be truly tuberculous lesions; Pritchard 49 and Diguimbaye Djaibe et al, 50 also implied that viable mycobacteria may not be present in calcified lesions. The 7.5% culture positivity from the lesion current finding, was lower than 47% reported by Ameni et al, 51 35% reported by Müller et al, 52 32% reported by Shimeles, 53 31.4% reported by Woyessa et al, 54 and 23.6% reported by Araujo et al, 55 in slaughtered cattle, and 30.6% by Arega et al, 10 in swine. However, the present finding was higher than that of Aknaw et al, 56 who reported 2.9% in slaughtered cattle at Bishoftu abattoir.…”
Section: Discussionmentioning
confidence: 48%